Impressive predictive value of ankle-brachial index for very long-term outcomes in patients with cardiovascular disease: IMPACT-ABI study. - Takashi Miura (PLoS ONE, 2017)
The ankle-brachial index (ABI) is a marker of generalized atherosclerosis and is predictive of future cardiovascular events. However, few studies have assessed its relation to long-term future cardiovascular events, especially in patients with borderline ABI. We therefore evaluated the relationship between long-term future cardiovascular events and ABI.In the IMPACT-ABI study, a single-center, retrospective cohort study, we enrolled 3131 consecutive patients (67 ± 13 years; 82% male) hospitalized for cardiovascular disease and measured ABI between January 2005 and December 2012. After excluding patients with an ABI > 1.4, the remaining 3056 patients were categorized as having low ABI (≤ 0.9), borderline ABI (0.91-0.99), or normal ABI (1.00-1.40). The primary endpoint was MACE (cardiovascular death, myocardial infarction [MI] and stroke). The secondary endpoints were cardiovascular death, MI, stroke, admission due to heart failure, and major bleeding.During a 4.8-year mean follow-up period, the incidences of MACE (low vs. borderline vs. normal: 32.9% vs. 25.0% vs. 14.6%, P<0.0001) and cardiovascular death (26.2% vs. 18.7% vs. 8.9%, P<0.0001) differed significantly across ABIs. The incidences of stroke (9.1% vs. 8.6% vs. 4.8%, P<0.0001) and heart failure (25.7% vs. 20.8% vs. 8.9%, P<0.0001) were significantly higher in the low and borderline ABI groups than in the normal ABI group. But the incidences of MI and major bleeding were similar in the borderline and normal ABI groups. The hazard ratios for MACE adjusted for traditional atherosclerosis risk factors were significantly higher in patients with low and borderline ABI than those with normal ABI (HR, 1.93; 95%CI: 1.44-2.59, P < 0.0001, HR, 1.54; 95% CI: 1.03-2.29, P = 0.035).The incidence of long-term adverse events was markedly higher among patients with low or borderline ABI than among those with normal ABI. This suggests that more attention should be paid to patients with borderline ABIs, especially with regard to cardiovascular death, stroke, and heart failure.